2020
DOI: 10.1111/ijpo.12725
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and cardiovascular outcomes in three‐year‐old children of participants inUPBEAT, anRCTof a complex intervention in pregnant women with obesity

Abstract: Summary Background Maternal obesity is associated with offspring cardiometabolic risk. UPBEAT was a randomised controlled trial of an antenatal diet and physical activity intervention in 1555 women with obesity. The intervention was associated with lower gestational weight gain, healthier diet and metabolic profile in pregnancy, and reduced infant adiposity at six months. Objective We have investigated whether the UPBEAT intervention influenced childhood cardiometabolic outcomes or was associated with sustaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 44 publications
(66 reference statements)
5
50
1
Order By: Relevance
“…The effective prenatal gestational weight gain intervention had no overall effect on child BMIz or skinfold thicknesses through 36 months. The observed BMIz and skinfold values and changes over time were highly consistent with other studies of pediatric populations of women with obesity [18][19][20][21][22]. The observational literature and developmental origins of disease hypothesis suggest that reducing excess weight gain during pregnancy should lower offspring risk of obesity [3].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The effective prenatal gestational weight gain intervention had no overall effect on child BMIz or skinfold thicknesses through 36 months. The observed BMIz and skinfold values and changes over time were highly consistent with other studies of pediatric populations of women with obesity [18][19][20][21][22]. The observational literature and developmental origins of disease hypothesis suggest that reducing excess weight gain during pregnancy should lower offspring risk of obesity [3].…”
Section: Discussionsupporting
confidence: 87%
“…However, to date, prenatal lifestyle interventions have yielded mixed results on obesity risk during childhood [6]. Some positive effects were observed in a UK-based prenatal intervention targeting glycemic index, which also reduced gestational weight gain; the prenatal intervention reduced infant adiposity at 6 months [23] and had suggestive effects of lower odds of overweight/obesity at 3 years [22]. Also, a Finnish prenatal probiotic intervention designed to prevent allergic diseases in children reported a tendency for lower BMI in offspring at 4 years [9].…”
Section: Discussionmentioning
confidence: 99%
“…Attrition of the study population may have resulted in selection bias. However, the UPBEAT population studied at the 3‐year visit was a representative sample of the main UPBEAT cohort 34 . Furthermore, while the findings are generalizable for clinical practice amongst women with obesity, they are not directly generalizable to the general population.…”
Section: Discussionmentioning
confidence: 86%
“…We have previously reported that the UPBEAT intervention did not affect any measure of adiposity/obesity in the 3‐year old children, 34 therefore, the data was treated as a cohort. Demographic results were expressed as mean ± SD (SD), median and interquartile range or percent and number as appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…The on‐going UPBEAT (UK Pregnancies Better Eating and Activity Trial) trial succeeded in reducing gestational dietary GI, however, there were no significant reductions observed in birthweight 20 . Similar to the ROLO cohort, this longitudinal study is assessing potential lasting impacts of behavioural pregnancy intervention, recently reporting a positive reduction in adiposity among the intervention children at 3 years of age 21,22 …”
Section: Introductionmentioning
confidence: 94%